Report of the Irrigation Inquiry Committee Appointed by the Government of Bombay 1938 - Planning Commission (Planning Commission, 1938)
The Government of Bombay appointed our Committee in their Resolution, Public Works Department, No. 1985 36. dated the 28th December 1937. The members met for the first time in Bombay on 6th January 1938. After preliminary consultation among ourselves and with some of the principal Government officers associated with irrigation we proceeded to draw up a detailed questionnaire. At the same time we began recording oral evidence, and the questionnaire, when ready, was issued to all irrigators’ associations, sugar companies and representative individual irrigators and to such officials and non-official gentlemen as were in our opinion likely to throw light on the problems referred to us for inquiry.
Government of Bombay